Sosialisasi Pencegahan dan Penanggulangan Kebakaran Hutan pada Anak-Anak di Desa - Diba, Farah; Arbiastutie, Yanieta; Mangurai, Silvia Uthari Nuzaverra Mayang (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Belaban Ella Village is one of the villages that meets daily needs by utilizing forest resources. Burning land clearance is the cheapest and most convenient way to meet basic demands. Forest fires may be started by the clearing of land, particularly in the dry season. The aim of this community service activity is to educate, particularly the student at SMPN 6 Belaban Ella Village, about the risks, prevent, and control the forest fires. The activities were carried out face to face at the village hall, Belaban Ella Village, Menukung District, Melawi Regency. The interactive lecture method was used to deliver knowledge to 31 participants. In the course of the activity, a questionnaire is used for monitoring and evaluation. The results of the questionnaire showed that participants' understanding increased by 94% after delivering knowledge related to forest fire prevention and control. The participants were excited to participate in the exercise because of the interactive way in which the content was delivered. By learning about the prevention and control of forest fires, students may develop a greater awareness of environmental issues and help to reduce the number of forest fires.